IMPLEMENTATION OF RFID AND NODE-RED DASHBOARD IN THE SYSTEM ASSET MANAGEMENT AT PT. PAMAPERSADA NUSANTARA HEAD OFFICEJAKARTA - Prayoga, Yudi; Rijadi, Bloko Budi; Wismiana, Evyta (Teknik Elektro Universitas Siliwangi, 2024)
ABSTRACTImplementation of RFID technology and Node-RED dashboard in the asset management system at PT. Pamapersada Nusantara Head Office Jakarta. The aim of this research is to ensure the use and integration of RFID components in the implementation of a stock management system. The testing stages include ensuring the accuracy of reading RFID tags by the RFID reader, ensuring network connectivity between RFID components (RFID reader, RFID controller, and re terminal), as well as testing sending data from RFID tags read by the RFID reader to the MongoDB database via Node-RED . The Node-RED dashboard facilitates real-time inventory monitoring and management, registration of new assets, and status updates of assets stored in the warehouse space. The research results show successful implementation of RFID and Node-RED technology, which improves goods tracking and operational efficiency. Recommendations include improving the durability of RFID tags, maintaining network stability, optimizing dashboard usability, ensuring data integrity, scaling usage for future needs, increasing security measures for data storage and to create a smarter asset management implementation, it is necessary to create an item registration or description menu. condition of IN goods and description of the condition of goods OUT automatically. This research contributes to the development of an asset management system through the integration of RFID technology and the effective use of dashboards, especially the use of the Node-RED dashboard which can display data in real-time.Keywords: stock management, RFID, Node-RED, Node-RED dashboard, MongoDB